Virtual states : the Internet and the boundaries of the nation-state - Everard, Jerry, 1956- (Technology and the global political economy., 2000)
This text analyses the role of the state in a globalising, wired society. The author argues that while information technology poses fundamental challenges to the state, this will mean not the decline but rather the mutation of the state.